2015
DOI: 10.1128/jcm.03590-14
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Public Health Risk of Shiga Toxin-Producing Escherichia coli by Use of a Rapid Diagnostic Screening Algorithm

Abstract: dShiga toxin-producing Escherichia coli (STEC) is an enteropathogen of public health concern because of its ability to cause serious illness and outbreaks. In this prospective study, a diagnostic screening algorithm to categorize STEC infections into risk groups was evaluated. The algorithm consists of prescreening stool specimens with real-time PCR (qPCR) for the presence of stx genes. The qPCR-positive stool samples were cultured in enrichment broth and again screened for stx genes and additional virulence f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 50 publications
1
33
1
Order By: Relevance
“…Biochemical profiles also play a central role in the isolation and preliminary identification of E. coli strains in general, on media such as McConkey and eosin methylene blue agar, and of EHEC on sorbitol MaConkey (SMAC) agar and CHROMagar STEC medium (de Boer et al, 2015). …”
Section: E Coli Subtypesmentioning
confidence: 99%
“…Biochemical profiles also play a central role in the isolation and preliminary identification of E. coli strains in general, on media such as McConkey and eosin methylene blue agar, and of EHEC on sorbitol MaConkey (SMAC) agar and CHROMagar STEC medium (de Boer et al, 2015). …”
Section: E Coli Subtypesmentioning
confidence: 99%
“…Genomic information is highly complex, and there are many knowledge gaps with respect to the significance of various marker genes to public health [76]. Nonetheless, there is a growing body of evidence linking certain well-defined gene markers to virulence characteristics of bacteria, for example, the role of intimin (coded by the eae gene) in the pathogenesis of STEC, epidemiological associations between certain serotype features and outbreaks of serious foodborne illness (e.g., L. monocytogenes serogroups 1/2a, 1/2b, and 4b, STEC serogroups O26, O45, O103, O111, O121, O145, and O157), and even the type of toxin secreted (e.g., Shiga toxin 2) and the attendant severity of illness [77,78].…”
Section: Is It Dangerous? Rapid Identification Of Virulence Antimicrmentioning
confidence: 99%
“…Most of these strains are eae negative (71), so their presence in humans has not received much attention. However, in some studies 10 to 15% of clinical samples from patients with diarrheal illnesses have been positive for stx 1c and/or stx 2b (22,26,32,47).…”
Section: Stx Types and Subtypesmentioning
confidence: 99%
“…The Stx2b subtype was proposed to designate a strain subtype with a variant of the stx 2c gene but that did not cause HUS (124). Analysis of STEC in Europe revealed that stx 2b alone or together with stx 1c is common in STEC from deer droppings and wildlife populations (71, 106) but does not appear to cause severe human illness (21,27,32,47). The Stx2e subtype is mostly found in isolates from pigs and pork meat (9) and is commonly associated with pig edema disease (7).…”
Section: Stx Types and Subtypesmentioning
confidence: 99%